Praktik Demokrasi Pasca-Pemilu di Tingkat Lokal: Preferensi para Aktor Elite dalam Perspektif Teori Pilihan Rasional - Ruman, Yustinus Suhardi (Bina Nusantara University, 2015)
Electoral democracy generates the political elites. Because these political elites are born through a democratic process, they are expected to practice their power in accordance to the basic principles of democracy. One of them is to open the opportunity and acces of people to participatie in decision making proceses. Nevertheless, the problem is that the political elites who were elected through electoral democracy tend to close the participation of citizen in policy making process. To analyze how the political elites formulated the policy and what the rationality of the policy was, this article used rational choice theory. Article used secondary data to analyze the problem. Results of the analysis showed that democracy in local level after elections was determined by rationality, preferences, and interests of the political elites. The practices of power of the elites in local level in the context of rational choice theory made opportunity and access for the people obstructed. It then affects the existing development policies reflect only rationality, preferences, and interests of some elites.